Revealing the Satellite DNA Content in Ancistrus sp. (Siluriformes: Loricariidae) by Genomic and Bioinformatic Analysis - Dos Santos, Gabriel Esbrisse [UNESP]; Crepaldi, Carolina [UNESP]; Da Silva, Marcelo João [UNESP]; Parise-Maltempi, Patricia Pasquali [UNESP] (Karger Publishers, 2024)
Introduction: Eukaryotic genomes are composed of simple, repetitive sequences, including satellite DNAs (satDNA), which are noncoding sequences arranged in tandem arrays. These sequences play a crucial role in genomic functions and innovations, influencing processes such as the maintenance of nuclear material, the formation of heterochromatin and the differentiation of sex chromosomes. In this genomic era, advances in next-generation sequencing and bioinformatics tools have facilitated the exhaustive cataloging of repetitive elements in genomes, particularly in non-model species. This study focuses on the satDNA content of Ancistrus sp., a diverse species of fish from the Loricariidae family. The genus Ancistrus shows significant karyotypic evolution, with extensive variability from the ancestral diploid number. Methods: By means of bioinformatic approaches, 40 satDNA families in Ancistrus sp., constituting 5.19% of the genome were identified. Analysis of the abundance and divergence landscape revealed diverse profiles, indicating recent amplification and homogenization of these satDNA sequences. Results: The most abundant satellite, AnSat1-142, constitutes 2.1% of the genome, while the least abundant, AnSat40-52, represents 0.0034%. The length of the monomer repeat varies from 16 to 142 base pairs, with an average length of 61 bp. These results contribute to understanding the genomic dynamics and evolution of satDNAs in Ancistrus sp. Conclusion: The study underscores the variability of satDNAs between fish species and provides valuable information on chromosome organization and the evolution of repetitive elements in nonmodel organisms.
Keywords: Fish genomics; RepeatMasker; Repetitive DNA